Air Rescue for Pediatric Trauma in a Metropolitan Region of Brazil: Profiles, Outcomes, and Overtriage Rates - Colbachini, Paulo C. M.; Marson, Fernando A. L.; Peixoto, Andressa O.; Sarti, Luisa; Fraga, Andrea M. A. (Frontiers in Pediatrics, 2022)
Besides ensuring a quick response and transport of trauma victims, helicopter support also involves risks to patients and professionals and has higher operational costs. Studying prehospital triage criteria and their relationship with patient overtriage and outcomes is important, particularly in newly established services and in developing countries with limited health budgets. This could help improve the use of the helicopter rescue and provide better management of the costs and risks related to it. The objective of this study was to determine the epidemiologic and severity profiles of pediatric victims of trauma attended by helicopter in a Brazilian Metropolitan Area to evaluate the outcomes and overtriage rates related to pediatric air rescue in the region. We conducted an observational and retrospective study using 49 hospital and prehospital records from victims of trauma aged <18 years old (yo) assisted by helicopter and then transferred to a tertiary University Hospital. Of the 49 patients, 39 (79.6%) individuals were male, and the mean age was 11.3 yo. Vehicular collisions accounted for 15 (30.6%) of the traumas, and traumatic brain injuries occurred in 28 (57.1%) cases. A total of 29 (59.1%) individuals had severe trauma (Injury Severity Score; ISS >15), and 34 (69.4%) required admission to the intensive care unit. Overtriage varied from 18.4 to 40.8% depending on the criteria used for its definition, being more frequent in individuals aged between 1 to 5 yo. Death occurred in 10 (20.4%) patients. On prehospital evaluation, we classified 29/32 (90.6%) patients with severe trauma according to the Pediatric Trauma Score (PTS ≤8) and 18/25 (72%) according to the Revised Trauma Score (RTS ≤11). Of these, 7/29 (24.1%) and 6/18 (33.3%), respectively, presented ISS <15 at in-hospital evaluation. None of the patients with PTS >8 and 3/7 (42.8%) of those with RTS >11 presented ISS >15. In conclusion, air rescue of pediatric trauma victims was used mainly for critically ill individuals, resulting in rates of overtriage compatible with that found in the literature. PTS showed the lowest rates of overtriage within excellent rates of undertriage.